Studies on genetic variability, heritability and genetic advance in fenugreek (Trigonella foenum-graecum L.) - N Hariprasada Rao, C Sarada, K Giridhar (Journal of Spices and Aromatic Crops, 2008)
The present investigation was carried out with fenugreek genotypes obtained from differentcoordinating centers of AICRP on Spices. Pods per plant (36.5 and 34.61), number of seedsper pod (22.86 and 21.20) and seed yield (22.09 and 17.21) recorded highest coefficients ofvariation (both phenotypic and genotypic), while it was low for pod length (11.43 and 7.32).Heritability estimates were high for plant height (83.10), pods per plant (89.90) and seeds perpod (86.00). Seed yield (60.70) and branches per plant showed moderate estimates of heritability.The characters viz. plant height, pods per plant, seeds per pod and seed yield which recordedhigh heritability also showed high genetic advance indicating operation of additive geneaction in the inheritance of these traits. These studies indicated that selection may beworthwhile in fenugreek for number of pods per plant, seeds per pod besides plant heightfor achieving higher yields.